GPS Ice Flow Measurements, Allan Hills, Antarctica - Hamilton, Gordon S.; Kurbatov, Andrei V.; Spaulding, Nicole; Spikes, Vandy Blue (IEDA: US Antarctic Program Data Center, 2011)
This data set includes includes high-precision GPS measurements of steel poles within the Allan Hills Main Ice Field, Near Western Ice Field, and extending to the eastern edge of the Middle Western Ice Field, in Antarctica. These data were collected between December 1997 and December 2010. The extended survey period allowed for vertical and horizontal velocities to be calculated with low associated error. Parameters include locations of poles in latitude and longitude, as well as elevation, ice velocity, and accumulation rates. Data are available via FTP as ASCII text files in comma separated value (.csv) format. Raw data are also provided as Trimble raw data, compressed in .zip format, and supplementary information is provided in .csv format and portable document format (.pdf).